Studi Literatur: Strategi Penguatan Literasi Lingkungan pada Peserta Didik di Sekolah - Pohan, Indah Ramadhani; Mahardika, Nabila; Susanti, Rahmi; Amizera, Susy (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Low environmental literacy is caused by a lack of environmental literacy reinforcement, necessitating strategies through four aspects of environmental literacy. This study aims to explore strategies for strengthening students' environmental literacy in schools. This study used a literature review method by reviewing 12 articles from the Google Scholar and Garuda databases published between 2021 and 2024. Data analysis was conducted by identifying patterns, differences, and potential reinforcement strategies. Based on the results of the journal review, there are differences in reinforcement strategies at the three levels of education. At the elementary school level, the strategy focuses on introducing students to the environment to foster environmental awareness. Furthermore, at the junior high school level, students are directed to further develop understanding and skills through environmental project activities. Then, at the senior high school level, students are directed to further strengthen environmental literacy through concrete action activities related to the environment.